Factors Contributing to Stress Among Parents of Children with Autism - Hassan , Komal; Inam , Attiya (Nurture, 2013)
Numerous autistics have behavior repertoires that might be predicted to have an impact on the family. The proposed study was designed to gauge the different factors contributing to stress among parents of children with autism between the ages of 3-14years. Study was carried out at five institutions of Lahore on a purposively selected sample of eighty parents (both fathers & mothers) of forty children with autism. A self prepared structured interview schedule named as Parental Stress Catalog (PSC) was used for collecting information from the parents. Descriptive statistical measures as well as independent samples t-test was used to analyze the collected data. Percentages, means and SDs of the responses, regarding different factors contributing to parental stress were found. T-test was applied to verify the differences between mothers’ and fathers’ responses. Results revealed a considerable amount of stress among parents of children with autism. There were various factors (psychological, social, educational, financial and future concern) identified which caused stress in parents having children with autism but future concern of the child was a factor in which parents experienced more stress than other factors. The study also revealed that mothers suffered more stress than fathers; they consequently require special attention and counseling services from professionals.